Alveolar Echinococcosis in Children. (11th May 2020) - Jonaitytė, Emilija; Judickas, Martynas; Tamulevičienė, Eglė; Šeškutė, Milda
Abstract : Alveolar echinococcosis (AE) is an infectious zoonotic disease that is caused by Echinococcus multilocularis . The disease is generally identified accidentally because of the long asymptomatic period, has a malignant behaviour, and mainly occurs in the liver. Usually it is diagnosed in adults and is very rare in pediatric patients. We report two cases of AE and 1 differential case between AE and cystic echinococcosis (CE) in children: two of them had lesions in the liver and one had rare extrahepatic presentation of a cyst in the spleen. All our patients received chemotherapy with albendazole because surgical treatment was not recommended. The children were followed-up from 10 to 30 months and no significant improvement was seen. In this report we discuss the difficulties we faced in the treatment and follow-up of these patients. We also review the main clinical manifestations, general diagnostic methods, and treatment options of AE according to the current literature.